Role of magnetic field on forced convection of nanofluid in a branching channel - Selimefendigil, Fatih; Öztop, Hakan Fehmi; Chamkha, Ali J. (Emerald Group Publishing Ltd, 2020)
Purpose Numerical study of nanofluid forced convection within a branching channel was performed under the influence of a uniform magnetic field. The purpose of this study is to enhance the heat transfer performance of the separated flow at the branching channel with the use of magnetic field and nanofluid. The use of magnetic field and enhancement in both the thermal conductivity and electrical conductivity with the inclusion of the nanoparticles provides favorable thermophysical properties of the nanofluid when it used as a heat transfer fluid in a branching channel. The results of this study may be used to control the thermal performance in a branching channel and further optimization studies in the presence of magnetic field. Design/methodology/approach Galerkin weighted residual finite element method was used for the simulations. The numerical simulation results are performed by changing the inclination angle of the lower branching channel (between 0 degrees and 90 degrees), thermophysical properties of the fluid via inclusion of nanoparticles (between 0 and 0.04), Reynolds number (between 100 and 400) and magnetic field strength (Hartmann number changes between 0 and 15). Findings It was observed that the recirculation zones and reattachment length of the upper and lower branching channels are affected by the variation of those parameters. Reattachment lengths increase with the augmentation of the Reynolds number and deterioration of the Hartmann number. Average Nusselt number becomes higher for higher values of Hartmann number and solid particle volume fraction. Inclusion of the nanoparticle to the base fluid is very effective for the configuration with higher values of Hartmann number. An optimum value of the inclination angle of the lower branching channel is observed, beyond which heat transfer rate is significantly reduced due to the establishment of a large vortex in the upper branching channel and restriction of the fluid motion. Originality/value In this study, forced convection of nanofluid flow in a branching channel under the effect of magnetic field was numerically studied. Magnetic field effects with nanoparticle inclusion to the base fluid on the convective heat transfer was analyzed for various inclination angles of the lower branching channel. Flow separation at the junction of the channels and thus convective heat transfer rate are influenced by the variation of these parameters. There are many studies related to application of the magnetic field with nanofluids, and a few of them are related to configurations with separated flows. To the best of the authors' knowledge, there exist no studies for the application of nanofluids and magnetic field for the convective heat transfer in a branching channel. This topic is of importance as there are many engineering applications of the branching channels.
Keywords: Finite element method; Nanofluid